Implementation of Comprehensive Agrarian Reform Program of a Municipality in Negros Occidental - Ramos, Kim C. (Philippine Social Science Journal)
The implementation of land reform programs has become the point of issue in many parts of Asia, including the Philippines. This descriptive-comparative study determined the extent of implementation of the Comprehensive Agrarian Reform Program (CARP) among the Agrarian Reform Beneficiaries (ARBs) and implementers. Using the researcher-made questionnaire, 189 ARBs who are cultivating the CARP covered lands, and 9 CARP implementers provided data for this study. Aided by descriptive-comparative statistics, findings showed a great extent of implementation. It further revealed a significant difference in the extent of implementation of CARP as assessed by the ARBS and implementers. However, it showed no significant difference when ARBs were grouped according to the size of landholding, land tenure status, and crops planted. Moreover, there are challenges identified in the implementation of CARP that should be addressed by the DAR and other national government agencies involved in the implementation.